Desarrollo de un curso virtual de photoshop para la asignatura de Diseño Tridimensional 3D, del tercer ciclo de la carrera de Artes Plásticas, de la Universidad Nacional de Loja, del área de la Educación, el Arte y la Comunicación, periodo 2015 - Cabrera González, María Dolores (2015)
Currently, educational processes have undergone several changes from traditional school to use technology, virtual courses being indispensable for access to content by teachers and students resort. This research is based on the construction of a Virtual Learning Course for 3D Dimensional Design students of the School of Plastic Arts at the National University of Loja, it is intended to be used as a learning tool and mediator of the teaching. This research was developed with the ADDIE model, which allowed its construction that meets the requirements of teachers and students to improve their learning process. Among the most important results include the direct relationship between the content posted on the online course and syllabus of the race, and the assimilation of resources and activities in the same by students. Considering these elements it is concluded that the development of online course contributed to the improvement of teaching and learning processes of the School of Visual Arts in direct relation to the syllabus of the race which ensured an end product quality. In the development of this research, it is necessary to clarify that there is a high percentage of students in the field of 3D three-dimensional design that has an affinity for technology and skills to use and internet access. Note that when exposed to the virtual course their affinity with the subject improved significantly